Strengthening National Awareness Among Elementary Students at The Republic of Indonesia School in Tokyo - Loretha, All Fine; Windiarti, Rina; Amin, Zakki Nurul; Sariah, Qoniatus (Journal of Innovation and Research in Primary Education, 2025)
Initial study found out a lack of awareness, understanding, and interactive experience of students at the Republic of Indonesia School Tokyo about Pancasila and Indonesian Culture. Only about 6.2% of students managed to answer questions correctly on the national insight material. Meanwhile, the survey results showed that 28.6% of students understood Pancasila in class, while 21.7% of students understood it from social media. This study aims to determine the effect of interactive modules based on Pancasila student profiles on national insight at the Republic of Indonesia Elementary School Tokyo. The research method used was a quantitative one-group pretest-posttest experiment. The subjects of the study consisted of 17 male and female students in grade 1 of the Republic of Indonesia Elementary School Tokyo in phase A, namely ages 6-8 years. The research method used was a quantitative experiment, One-group pretest-posttest. The research subjects comprised 17 male and female students of grade 1 of the Republic of Indonesia Elementary School Tokyo in phase A, aged 6-8 years.The study results showed a significant increase in the national insight of elementary school children after utilizing the interactive module. Based on the hypothesis testing, the p-value is 0.000 <0.05. By implementing interactive modules that integrate the IPTEKS approach and project-based learning methods, students become more active and enthusiastic in understanding and applying the values of diversity.